Decision Support System for Housing Subsidies - Nugraha, Adhi (Jurnal Teknik Industri, 2020)
The house is one of the basic human needs besides clothing and food. However, not all residents in Indonesia are able to meet these needs. Therefore, the government provides subsidized homeownership programs for the middle to lower classes. The decision to grant a subsidized house is very complicated. Therefore, this research aims to provide a decision-making system in determining the right recipient of subsidies. The method used is weighting and pairwise comparison. The results show that the decision support system of the proposal is able to provide alternative decisions on the provision of home subsidies.